On the 60th anniversary of Igor V. Vachkov - K.A. Bochaver (Клиническая и специальная психология)
The article is dedicated to the anniversary of professor Igor V. Vachkov, which took place in December 2024. The main stages of the professional development of this outstanding psychologist-practitioner and scientist are described. Igor Vachkov has many professional roles. He is better known to some as a methodologist of practical training work. Others know him as the author of the polysubjective approach in the psychology of education. Many people are interested in the method of fairy tale therapy created by him in his applied work. The article helps to learn about him as a scientific supervisor, editor-in-chief of “Clinical psychology and Special Education” journal, and even a poet. We congratulate dear Igor Vachkov and wish him all the best, good health and happiness!